Mapping the binding site of a cross-reactive Plasmodium falciparum PfEMP1 monoclonal antibody inhibitory of ICAM-1 binding - Lennartz, F; Bengtsson, A; Olsen, R; Joergensen, L; Brown, A; Remy, L; Man, P; Forest, E; Barfod, L; Adams, Y; Higgins, M; Jensen, A (American Association of Immunologists, 2015)
The virulence of Plasmodium falciparum is linked to the ability of infected erythrocytes (IE) to adhere to the vascular endothelium, mediated by P. falciparum erythrocyte membrane protein 1 (PfEMP1). In this article, we report the functional characterization of an mAb that recognizes a panel of PfEMP1s and inhibits ICAM-1 binding. The 24E9 mouse mAb was raised against PFD1235w DBLβ3_D4, a domain from the group A PfEMP1s associated with severe malaria. 24E9 recognizes native PfEMP1 expressed on the IE surface and shows cross-reactivity with and cross-inhibition of the ICAM-1 binding capacity of domain cassette 4 PfEMP1s. 24E9 Fab fragments bind DBLβ3_D4 with nanomolar affinity and inhibit ICAM-1 binding of domain cassette 4-expressing IE. The antigenic regions targeted by 24E9 Fab were identified by hydrogen/deuterium exchange mass spectrometry and revealed three discrete peptides that are solvent protected in the complex. When mapped onto a homology model of DBLβ3_D4, these cluster to a defined, surface-exposed region on the convex surface of DBLβ3_D4. Mutagenesis confirmed that the site most strongly protected is necessary for 24E9 binding, which is consistent with a low-resolution structure of the DBLβ3_D4::24E9 Fab complex derived from small-angle x-ray scattering. The convex surface of DBLβ3_D4 has previously been shown to contain the ICAM-1 binding site of DBLβ domains, suggesting that the mAb acts by occluding the ICAM-1 binding surface. Conserved epitopes, such as those targeted by 24E9, are promising candidates for the inclusion in a vaccine interfering with ICAM-1-specific adhesion of group A PfEMP1 expressed by P. falciparum IE during severe malaria.